The impact of typology capital on community empowerment programs: evidence from rural development in Indonesia - Sarjiyanto, Sarjiyanto; Mulki, Yoganingtisas Aulia; Istiqomah, Nurul (Jurnal Ekonomi & Studi Pembangunan, 2024)
The transition from the ancient paradigm, where communities were only seen as objects of development, to a new approach that emphasizes community involvement and collaboration with local institutions highlights the importance of empowerment and enriching the quality of communities. This evolution towards community empowerment is paramount for positive societal development in Indonesia, necessitating active participation from the community to attain the desired objectives. This study endeavors to ascertain the correlation between working capital, social capital, and psychological capital in community empowerment programs, as well as to discern which capital plays a more substantial role in empowering the community in Karangasem village. Utilizing a quantitative method, data was collected through questionnaires from 255 community beneficiaries of the empowerment program in Karangasem Village, Sukoharjo, Central Java, Indonesia. Structural Equation Modelling (SEM) was employed for analysis. The research indicates that various forms of working, social, and psychological capital significantly influence community empowerment programs. Working capital emerges as the most influential, with a noteworthy 78% significance, indicating its pivotal role in program implementation. Effective management and allocation of funds are imperative for capital utilization. Social capital, particularly networks, is vital in fostering community empowerment by enhancing internal and external connections. Psychological capital, characterized by optimism, fuels community engagement and commitment to empowerment initiatives, underscoring the importance of internal motivation in program success. These findings may serve as a basis for governmental and empowerment program managers to formulate policies to enhance community welfare.